Pengaruh Debt to Equity Ratio, Return on Assets, dan Return on Equity Terhadap Harga Saham pada Perusahaan Properti dan Real Estate di Bursa Efek Indonesia Periode 2018-2023 - Rafli Ahmad Adzikri (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study aims to explain the influence of the debt-to-equity ratio, return on assets, and return on equity on the stock prices of property and real estate companies. This research employs a quantitative method. The population of this study consists of property and real estate companies listed on the Indonesia Stock Exchange. The sample was selected using purposive sampling, comprising 10 companies based on their financial reports from 2018 to 2023, resulting in 60 data points. The analysis technique used is panel data regression analysis. This study uses secondary data, which can be obtained from the Indonesia Stock Exchange website accessible at www.idx.co.id. The data obtained were analyzed using the STATA 17 computer program. The study concludes that the debt-to-equity ratio has a negative and significant effect on stock prices, the return on assets has a positive but not significant effect on stock prices, and the return on equity has a negative but not significant effect on stock prices in the property and real estate sector.